تخطيط مدينة إسلامية بطابع حديث - مرعي, شيماء (My University, 2019)
ييدف البحث تؾضيح مفاىيؼ التخظيط شكل عام ومؽ ثؼ التركيز على مفيؾم التخظيط العم ا رني وتؾضيح اىميتو وابرز عناصره , ومؽ ثؼ يتجو البحث الى تؾضيح مفيؾم المدن وانؾاعيا والعؾامل التي تداعد في تدمية التجمعات بالمدن او القرى , بعد ذلػ يدور البحث على حؾل مفيؾم المدينة الاسلامية وتؾضيح نذأتيا وعيؾرىا في المجتمع العربي القديؼ وتظؾره مؽ مرور الزمؽ , ويعرض البحث بعض مؽ نغريات التخظيط الاسلامي القديؼ ونغريات التخظيط الحديث ويعمل على المقارنة فيما بينيا , يعرض البحث مجمؾعة مؽ الحالات الد ا رسية الاسلامية القديمة في مناطق متفرقة , ومؽ ثؼ يتجو لاختيار المؾقع المناسب لاقامة المدينة الاسلامية الحديثة عليو , بعد تحليل لمجمؾعة مؽ المعايير تؾصل البحث الى المؾقع المناسب شرقي محافغة أريحا والاغؾار بحيث انو يحتؾي على اغلب المعايير الميمة لاقامة المدينة عليو . ييدف البحث الى الخروج بمخظط استخدامات للا ا رضي او مخظط رئيدي للمدينة الاسلامية بحيث يجمع ما بيؽ طابع المدينة الاسلامية القديؼ والظابع الحضري الحديث للتظؾر يعمل على تلبية احتياجات سكانيا مؽ كافة النؾاحي , حيث تؾفر الفرص والخدمات الذي يمنحيا ذلػ ويعظييا طابع التكامل والقابلية للتجديد والتؾسع المدتقبلي . The research aims at clarifying the concepts of planning in general form and then focusing on the concept of urban planning and clarifying its importance and its most important elements. Hence, the research aims at clarifying the concept of cities and their types and the factors that help in naming communities in cities or villages. The research then revolves around the concept of the Islamic city and clarifying its origin and appearance In the old Arab society and its evolution from time to time, the research presents some of the theories of ancient Islamic planning and modern planning theories and works to compare them. The research presents a collection of old Islamic study cases in different areas, For the establishment of the modern Islamic city, after an analysis of a set of criteria, the search to the appropriate location east of Jericho and the Jordan Valley so that it contains most of the important criteria for the establishment of the city. The aim of the research is to find a plan for the use of land or a master plan for the Islamic city, which combines the character of the old Islamic city with the modern urban character of the development, which will meet the needs of its inhabitants in all aspects, providing the opportunities and the services it gives and giving them the nature of integration and the possibility of renewal and future expansion